Business events at a spa destination: an insight into senior participant motivation. Issue 1 (3rd January 2020) - Dimitrovski, Darko; Seočanac, Marijana; Luković, Maja
Abstract : Purpose: The purpose of this paper is to examine the motivation of the attendees of the Annual Meeting of the Serbian Association of Seniors. The research aims to segment the senior participants according to their push and pull motivations for attending association meetings, by using cluster analysis to understand the role of destination personality in the segmentation process. Design/methodology/approach: The questionnaire, based on a seven-point Likert scale, was distributed among representatives and members of the Association of Pensioners of Serbia. The data collected were assessed with the use of SPSS 21 statistical software. Findings: The results of the study reveal the most important push and pull motives that drive senior citizens to take part in this type of event. It has also provided a better understanding of senior business event participants in relation to destination personality. Research limitations/implications: The data were collected from 124 questionnaires. In order to provide a more detailed insight into the senior citizens' motivation to participate in events, a larger sample would be required. Practical implications: The research findings provide valuable information about senior business event visitor behaviour, which is of high importance for destination marketers and managers. Originality/value: Nowadays, business events motivation research is generally focussed on middle-aged and young attendees, so insight into the perception of senior citizens related to business event motivation provides a further understanding of this specific consumer segment. Additionally, gaining insight into seniors' perspectives related to participation in association meetings after retiring from work assists in comprehending the complex nature of their motivation to participate in these types of business events, as well as underlining the fact that senior business event attendees have been, up until this point, largely neglected as a group in terms of similar research.